Family experience of childhood obliterative bronchiolitis – findings from a UK and Ireland national survey. (24th May 2012) - Austin, S; Thompson, L; Connett, G; McGinnity, T
Abstract : Aims: To highlight areas of worry and concern, as well as excellence, and to share results to improve the overall care of children with OB in the UK and Ireland. Method: Family questionnaire to explore the experiences of families who have a child affected by Obliterative Bronchiolitis (OB). A printed survey including SAE was sent to 29 families, followed up by an on-line reminder. The key areas covered were: diagnosis, treatment and care, support services and sources of information. Results: There was a 70% return rate to the survey. Of these 43% of families were initially misdiagnosed. Overall findings were of lack of awareness and knowledge amongst some professionals, and lack of information and support for families. Time to diagnosis and quality of ongoing management were particular areas of concern. Breathtakers and the respiratory consultant were seen as the main sources of reliable information. Variations in the level of care nationally were picked up, raising concerns about equity of access to the best standards of care. Conclusions: Support groups and charities are vitally important for all sufferers of rare diseases. To address the issue of 'repeating stories', the information from this survey has been used to develop a route map for the optimal care of children with this condition. This will provide a comprehensive resource for families and professionals planning the care of OB sufferers in the UK.